Wall ball - Markey, Kevin (New York : Harper, 2010)
As the boys of the Rambletown Rounders get ready for another baseball season, spring training is taking place in the snowiest weather Rambletown has ever seen.
Ages 8-12.
Keywords: Baseball -- Fiction; Snow -- Fiction; Schools -- Fiction